Intranasal Tooth - An Ectopic Eruption of Mesiodens in Nasal Cavity: A Case Report and Review - R Guru Prasad; Preeti P Nair; Harshkant Gharote; Karthik Hegade; Kavita Agarwal; Arpit Jain (Wolters Kluwer Medknow Publications, 2011)
An intranasal tooth (INT) is an ectopic tooth erupting into the nasal cavity. It is a rare clinical entity. Ectopic and supernumerary teeth may be present in many regions of maxillofacial skeleton. Ectopic teeth maybe supernumerary, deciduous or permanent. The clinical manifestations of intranasal tooth are quite variable and they may cause a variety of symptoms and complications. Their clinical and radiographic presentations are classical, posing little challenge to the diagnostician. The identification of such teeth can be important since they have potential to cause considerable morbidity. Here, we describe a case of intranasal tooth along with possible etiopathogenesis, clinical and radiographic features, differential diagnosis, potential complications and treatment modalities.